Risk of rupture of the cerebral aneurysm in relation to traumatic brain injury using a patient-specific fluid-structure interaction model. (July 2019) - Razaghi, Reza; Biglari, Hasan; Karimi, Alireza
Highlights: Patient-specific FSI model of the skull, brain, and cerebral aneurysm was established. The aneurysmal artery wall stresses and deformations under frontal TBI were analyzed. Higher stresses in the aneurysmal artery wall were observed after TBI. Higher blood pressures were observed in the aneurysmal artery wall after TBI. TBI by inducing concentrated stress can increase the risk of aneurysm rupture. Abstract: Background and objective: Cerebral aneurysm, which is defined as one of the weakened area in the wall of an artery in the brain, ruptures when wall tension exceeds its mechanical strength. Traumatic brain injury (TBI) by exerting a sudden impact load to the brain can lead to mechanical failure of the cerebral blood vessels followed by an alteration in not only the structure but also the function of the cerebrovascular. TBI also alters the hemodynamics of the blood flow in the cerebrovascular, while it has been shown that hemodynamics has a key asset in the progression and rupture of the cerebral aneurysms. So far, there is a lack of knowledge on the risk of rupture of the cerebral aneurysm in relation to TBI. Therefore, this study aimed to calculate the mechanical stresses and deformations in the arterial wall as well as the pressure and velocity of the blood using a fluid-structure interaction (FSI) model of the cerebral aneurysm located in the anterior circulation region of the circle of Willis. Method: A patient-specific FSI model of the human skull, brain, and cerebral aneurysm, was established using human computed tomography (CT)/ magnetic resonance imaging (MRI) data and subjected to a frontal TBI. Results: The results revealed considerable increasing of ∼ 8 kPa (60 mmHg) and 0.40 m/s in the pressure and velocity of the blood in the intraluminal of the cerebral artery after TBI. The von Mises stress, shear stress, and deformation of the cerebral aneurysm wall also showed the increasing of 56.03 kPa, 15.66 Pa, and 0.072 mm after TBI, respectively. Conclusions: Although the injury to the aneurysm wall after TBI is lower than that of the aneurysm wall mechanical strength, it still can alter the stress pattern in the wall and disrupt the hemodynamics of the blood. These results have implications in understanding the rupture risk of the cerebral aneurysm due to TBI, which may contribute in establishing preventive and/or treatment methods.